Information Society and Globalization – Realities and Challenges - Vassilev, Yordan; Petkova, Elitsa (Research Papers, 2020)
In the present world economy there is a fundamental transformation that affects all spheres of human life.The aim of the article is to present the formation of the information society under globalization and to outline the realities and challenges that stand for solving in the new conditions. The key importance of information and new technology for the social and economic development of countries is emphasized through a review of some basic theoretical concepts. As a result of the theoretical study, the positive and negative effects of globalization have been classified and analyzed.